Penambangan Emas Tanpa Izin dan Public Health: Studi Kualitatif di Nusa Tenggara Barat (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose:To analyze the factors influencing the implementation of regulation on the existence of Artisanal Small Scale Gold Mining (ASGM) in Alas District, Sumbawa Regency, West Nusa Tenggara Province.Method: This research is qualitative descriptive research with the determination of informants using snowball sampling. Data analysis using data analysis from Miles & Huberman.Results:Factors driving the number of unlicensed gold mining at Alas are economic factors. The availability of insufficient jobs and low economic status is the reason (ASGM) perpetrators retain jobs as illegal miners. Another factor is weak regulation. The government has not set the People Mining Area as a condition of issuing the Mining Permit for the People so that (ASGM) operations are still operational.Conclusion: The dominant factor causing PETI sustainability in Alas sub-district is the economic factor. Policies on the existing mineral mining can not function properly because Alas sub district has not been determined by the mining area of the people so that people do not get the permits of the people's mining